THE SEPARATION OF POWERS AND PRINCIPLES OF STATE POLICY - Tomy Michael (International Journal of Law in Changing World)
This article examines the main points of state policy, which is more popularly known as the Outlines of State Policy (GBHN), but in fact, the two meanings are very different. Referring to the Decree of the People's Consultative Assembly of the Republic of Indonesia Number IV/MPR/2014 concerning the Recommendation of the People's Consultative Assembly of the Republic of Indonesia for the 2009-2014 Term of Office, specifically in Point 10 it is written to reformulate the national development planning system with the GBHN as model.  Although the GBHN was rejected, it became a reference. Before the reform, the GBHN in state administration made the People's Consultative Assembly (MPR) the highest state institution. After the reform, it tends to follow the theory of separation of powers as the highest center for carrying out national life. This article employs Hans-Georg Gadamer's hermeneutical interpretation method. The principles of state policy must be understood in the context of the separation of powers, as this determines the application of power. This separation continues on the principle of sharing and checking. Separation of powers is not synonymous with democracy, but it is the origin of the state, allowing the formation of power to continue the state's existence.